2019
DOI: 10.20473/fmi.v55i3.15502
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychocurative on Cortisol Level, Anxiety, and Quality of Life in Advanced Stage Cervical Cancer Patients

Abstract: Every year, there are 500.000 new cases and more than 250.000 deaths caused by cervical cancerworldwide. Cervical cancer patients faced physical and psychological problems several times that it activate stress mechanism such as hypothalamus-pituitary-adrenal (HPA) axis. These recurrent activations caused HPA axis disruption and adverse clinical effects. Several symptoms of endocrine stress response are the change of circadian cortisol rhythm. Cortisol is known as a stress hormone that involves an organism's re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The correlation test results showed that there was a correlation between the duration of DMT2 and the incidence of diabetic peripheral neuropathy (p=0.000; odds ratio 0.038; 95% CI 0.005-0.271). This was consistent with some studies obtained a correlation between the duration of DM and diabetic neuropathy 16 . Research conducted by Fatkhur et al stated that the longer the patient suffering from DM, the risk of diabetic neuropathy was 16.7787 times greater in DM ≥5 years (p = 0.000).…”
Section: Discussionsupporting
confidence: 93%
“…The correlation test results showed that there was a correlation between the duration of DMT2 and the incidence of diabetic peripheral neuropathy (p=0.000; odds ratio 0.038; 95% CI 0.005-0.271). This was consistent with some studies obtained a correlation between the duration of DM and diabetic neuropathy 16 . Research conducted by Fatkhur et al stated that the longer the patient suffering from DM, the risk of diabetic neuropathy was 16.7787 times greater in DM ≥5 years (p = 0.000).…”
Section: Discussionsupporting
confidence: 93%
“…The sample size ranges from a minimum of 30 [ 24 , 35 ] to a maximum of 417 [ 6 ]. An equal sample size was used in the treatment and control group in 16 studies and an unequal sample size was used in 10 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding treatment trajectory, nine studies included patients receiving surgical treatment [ 6 , 25 , 27 , 32 – 34 , 36 , 44 , 46 , 48 ], seven studies included patients receiving chemotherapy [ 23 , 24 , 28 , 30 , 35 , 41 , 42 ], three studies included patients receiving surgery plus chemotherapy [ 26 , 40 , 47 ], two studies included patients receiving concurrent radio chemotherapy [ 37 , 39 ], two studies included patients receiving neoadjuvant chemotherapy [ 38 , 45 ], one study included patients receiving comprehensive anti-cancer treatment [ 43 ], one study included patients completed the definitive treatment of cervical cancer before two months [ 29 ] and one study included patients they had just get a diagnosis of cervical cancer and before starting of cancer treatment [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research that correlated the role of resistant cancer stem cells to cisplatin and the progression of many malignancies were included in ca mammae studies was reported that the presence of tumor cells were expressing the normal tumorigenic stem cell characteristics by 5.9% of the tumor cell population 3 . The population of these cells significantly increased to an average of 8.8% in primary transplants that only responded partially to cisplatin, while in secondary tumor transplants, the population increased to 22.8% 4 .…”
Section: Introductionmentioning
confidence: 95%